The moderating effect of corporate social responsibility on the impact of COVID-19 on stock prices of selected Philippine publicly listed firms - Fernandez, Maraiah L. (Animo Repository, 2022)
The contemporary view of corporate social responsibility (CSR) enabled firms to use it as a strategic tool to improve financial performance and assists them in mitigating financial risks during disasters. As the coronavirus disease 2019 (COVID-19) pandemic that impinges on economies and stock markets continues, companies sought to engage in CSR to protect their stock prices. However, few studies have proven the ability of CSR to mitigate the negative effects of disasters, especially during COVID-19. Hence, this study aims to investigate how CSR moderates the impact of COVID-19 on the stock prices of selected Philippine publicly listed firms. A sample of 58 out of 283 firms were classified as socially and non socially responsible based on their CSRHub ratings. The two groups’ average abnormal returns and cumulative average abnormal returns were then compared. Average abnormal returns is defined as the average unexpected gains or losses generated by a group of stocks in a given time. Meanwhile, cumulative average abnormal returns is the mean of all average abnormal returns of a group of stocks throughout the event window. Using an event study, one sample t-test, and Welch’s t-test, the study found that CSR mitigates the negative impact of COVID-19 on the stock prices of the selected Philippine publicly listed firms. Furthermore, it is determined that CSR only safeguards stock prices from the negative impact of disasters, but not necessarily adds on the stock price’s value. This study also provides recommendations to investors, managers, regulatory bodies, and future researchers. Keywords: corporate social responsibility, COVID-19, abnormal returns, event study